PENGARUH PERCEIVED RISK , KEPUASAN KONSUMEN TERHADAP INTENTION TO REVISIT DAN PURCHASE INTENT PADA KONSUMEN KASKUS WEBSITE DI SURABAYA - MULYONO, RONALD (Kajian Ilmiah Mahasiswa Manajemen, 2012)
Fast retail development makes the fast changes in retail so that the retail sales which was only traditionally turns into online. This study aims to determine Perceived Risk, Customer Satisfaction, Intention to Revisit, Purchase Intent in Kaskus Website to the consumer in Surabaya. The Sample used is 200 participated respondents and used SEM analysis (Structural Equation Modeling) through LISREL 8.70 program. The findings acquired from this study that H1, H4, H5 have positive effect while H2, H3 have negative effect. Limitations in this study are the number of respondents in this study is small enough so that it can’t represent the whole population in Surabaya and the respondents who shop the last 3 months in Kaskus Website so that the data is more accurate.